RISK LEADERS' COLLABORATION IN THE INDUSTRIAL 4.0 - I Wayan Wahyudi Antara; Anak Agung Ngurah Oka Suryadinatha Gorda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Commemorate the industrial 4.0 era, leaders are faced with new risks and challenges, ranging from adopting new technologies, and changing leadership styles to changing work environments that are increasingly digital and flexible. This research will focus on applying internet-based technology or the internet of things and the impact of risks on a leader in implementing his leadership in industrial 4.0. Seeing this as a unique phenomenon, researchers see a significant opportunity for risks that impact performance or affect one's activities as a leader in this industrial era 4.0. A research method is a qualitative approach with a purposive sampling technique. Data analysis in this study analyzes the results of observations, interviews, and documentation obtained from research using the Nvivo 12 Plus software. The data processing results in the study concluded that there were four primary nodes, namely Technology, Internet, Leaders, and IT Implementation Implications. In addition, primary Internet nodes are discussed most frequently in informant interviews. Good adoption and adoption, professional application processes, and wise and intelligent use can help reduce the risks and barriers to the application of internet technology to use its function positively to run and lead their respective companies.